2005
DOI: 10.1063/1.1869332
|View full text |Cite
|
Sign up to set email alerts
|

Size-selected cluster beam source based on radio frequency magnetron plasma sputtering and gas condensation

Abstract: We report on a source for producing size-selected nanoclusters based on the combination of radio frequency magnetron plasma sputtering and gas condensation. The use of plasma sputtering to vaporize a target is applicable to a large range of materials; Ag, Au, Cu, and Si have been attempted to date. The source, combined with a time-of-flight mass filter, can produce clusters in the size range from 2 up to at least 70 000 atoms, depending on the target material, with a constant mass (M) resolution (M∕ΔM∼25) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
227
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(234 citation statements)
references
References 30 publications
6
227
1
Order By: Relevance
“…An alternative interpretation of the principal role of helium in a magnetron source was put forward by Pratontep et al (2005). They suggested that the helium gas is itself involved in cluster formation in such a way that, with increased He flow there is a rise in the nucleation of small seeds which results in more but smaller clusters.…”
Section: Argon and Helium Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative interpretation of the principal role of helium in a magnetron source was put forward by Pratontep et al (2005). They suggested that the helium gas is itself involved in cluster formation in such a way that, with increased He flow there is a rise in the nucleation of small seeds which results in more but smaller clusters.…”
Section: Argon and Helium Supplymentioning
confidence: 99%
“…Thus, to enhance particle production and to steer its size distribution toward the desired range, it is valuable to have both empirical and conceptual insights into the effect of these parameters on the cluster formation process. Many papers have examined the effect of operating conditions on the size, morphology, and kinetic energy of nanoclusters (examples include Hihara and Sumiyama 1998; Morel et al 2003;Pratontep et al 2005;Das et al 2009;Quesnel et al 2010;Ayesh et al 2010;Gracia-Pinilla et al 2010;Nielsen et al 2010;Ganeva et al 2012;Luo et al 2012;Ayesh et al 2013;Bray et al 2014;Dutka et al 2015;Fischer et al 2015;Kusior et al 2016;Zhao et al 2016;Rudd et al 2017), but each typically looked only at a subset of source parameters. Consequently, a comprehensive multidimensional characterization has not yet been presented.…”
Section: Introductionmentioning
confidence: 99%
“…The clusters were created with a radio frequency magnetronsputtering cluster source and mass selected via a lateral time-of-flight mass filter. [38,48,49] The cluster beam impact energy was $15 eV/atom, so as to pin the clusters to the graphite surface upon landing. [37,50] In order to produce a uniform distribution across the entire surface of the support, the graphite substrate (10 Â 10 mm 2 ) was rastered (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A significant challenge arising is then how to accommodate and process this large abundance of clusters. The conventional cluster sources allow deposition onto planar substrates, a few square centimetres in area [11,18]. However, the MACS has the potential to cover with clusters an area of square metres (and in future beyond) in a matter of minutes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a standard stabilizer in colloidal synthesis of, e.g., catalytic nanoparticles [22][23][24][25][26][27][28]. For our proof of principle demonstration, PVP layers (either spray-deposited using a pulse valve or evaporated) were used as release layers, the support film was a carbon film produced using a direct-current evaporator or an e-beam evaporator, and the cluster layer comprised size-selected Au 923 clusters generated by a magnetron sputtering inert gas condensation cluster source [11] (thus in the demonstration a conventional cluster source only is employed). The characterization of the multilayer structure was performed using through-focal measurements with the aberration-corrected high angle annular dark field scanning transmission electron microscope (HAADF STEM).…”
Section: Introductionmentioning
confidence: 99%